Effect of miRNA-146a-mediated TLR4 Signal Pathway on the Pain of Lumbar Disc Herniation - Jing, Xiaowei; Gong, Zhiyuan; Li, Fangcai; Zhang, Ning; Xu, Zhengkuan; Chen, Qixin (Cellular and Molecular Biology, 2022)
The current experiment was carried out to explore the effect of the miR-146a-mediated TLR4 signaling pathway on the lumbar disc herniation pains. For this aim, a total of 32 rats were divided randomly into 4 groups – the blank group (Group C), Model group (M), miR-146a overexpression group (agomiR-146a group) and negative control group (NC group), with 8 rats in each group. Rats in Group M were prepared for the construction of lumbar disc herniation models, while those in the agomiR-146a group or NC group, in addition to the model construction, would receive the intrathecal injection of agomiR-146a or agomiRNA-146a NC. Thereafter, a series of tests were performed for rats, including the mechanical pain test and heat pain test to measure the pain threshold, RT-PCR to detect the expression of miR-146a, and the transcription of TLR4, IRAK1, TRAF6, IL-6 and TNF-α, Western blot to determine the expression of IRAK1 and TRAF6 and ELISA to determine the expression of IL-6 and TNF-α. Results showed that as compared to the blank group, rats in Group M were more sensitive to the pains, presenting with declines in the thresholds in the pain, and upregulation in the TRL4 signaling pathway (TLR4, IRAK1 and TRAF6) and pro-inflammatory factors, including IL-6 and TNF-α. In comparison with Group M, intrathecal injection of agomiR-146a relieved the pains, with significant upregulation of miR-146a and downregulation of TLR4, IRAK1, TRAF6, IL-6 and TNF-α. Then upregulation of miR-146a could reduce the activity of the TLR4 signaling pathway and the release of pro-inflammatory factors, which may be a potential strategy for the treatment of lumbar disc herniation.